COMPREHENSIVE TEACHER’S PROFESSIONALISM FOR CONTENT AND LANGUAGE INTEGRATED PROVISION - Anspoka, Zenta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Topicality of the problem is determined by several factors as well as the amendments on the Education Law and the General Education Law, which provide for a gradual transition to the acquisition of general secondary education in Latvian only, educational content reform and teachers experience to work in an ethnically and linguistically heterogeneous environment. The aim of the study is to analyse comprehensive school teachers theoretical background and practice experience to work in the content and language integrated teaching and learning approach. Because language not a subject only but a mean of acquiring other subjects in the comprehensive school, too, all teachers need theoretical knowledge and practical experience to plan and carry out two important tasks in the teaching/learning process – to help to students to acquire different subjects content and purposefully to use language for this. The research methods are analyses of theoretical literature and interviewing combined with classroom observations results. According research results the most important problems are insufficient knowledge about language role for acquisition of content, insufficient cooperation between teachers, part - understood issue, how to work with different texts as well as necessity to change attitude towards the pedagogical process and responsibility for learning outcomes.